Attenuation of the Calypso® system in a linear accelerator - Silva, Célia Patrícia dos Santos (2015)
Accuracy is the keyword when it comes to radiotherapy. More advanced treatments usually take more time, so immobilization is mandatory. However, immobilization does not resolve the intrafraction motion problem, whether it is caused by natural processes such as breathing and heart beating or patient intentional movement. This question led to the development of the Calypso® 4D Localization System. This is a system that monitors internal movement when treating allowing to interrupt and to correct any shift that occurs during treatment (intrafraction motion). That way it is possible to detect when the patient moves and also to account for internal movement. This technology was recently acquired and installed in Champalimaud Clinical Center. Considering that I am a radiation therapist in this center where the purpose is to ensure good quality of administered treatments, I could not do but to direct this work towards the field in which I dwell daily. It is advisable to study the effect of any new equipment in treatment delivery and that gives the opportunity to acquire and to explore local data. In the first part of this work, a review on state-of-the-art literature is provided (previously submitted in December 2013 and accepted in May 2014), as to allow for a fully comprehension of the subject discussed here: how Calypso® system works, its advantages when compared to other monitoring systems available and how it is being used around the world. After knowing how Calypso® works, one question is inevitable. In order to monitor the patient continuously an array is positioned above the patient during the treatment and the treatment planning system does not account for that. How much dose does the array attenuate? The second part of this work assesses this subject. A study was performed by measuring the transmitted radiation of several beams (with beam energy, field size and gantry angle variation) with and without the array in the beam path and the attenuation was calculated and analyzed (previously submitted in May). Finally, the third part of this work studies radiation attenuation in treatment tabletops. It was noted when Calypso® system was being installed that changing the treatment table was part of the installation process. For the system to work properly no electric conductive materials are allowed in the array’s volume detection, as the system functions by electromagnetic detection. Carbon fiber is an electric conductive material so the Varian Exact IGRT tabletop was replaced by a table with the two exchangeable inserts kVueTM Universal Tip Insert (carbon fibre) and kVueTM Calypso ® Varian Insert (kevlar). A study was performed in order to determine if there was any loss in treatment administration quality due to the radiation attenuated in the treatment tabletop. Radiation measurements were performed without tabletop and also with each of the three tabletops (with beam energy, field size and gantry angle variation). Attenuation was calculated for the three tabletops. It was assessed if new tabletops attenuated more or less radiation than the original one, and it was considered if it was adequate not to switch between kVueTM Calypso® Varian and kVueTM Universal Tip tabletops according to the use of calypso system or not, respectively. It is noteworthy that the Master Commission authorized the presentation of this work as three scientific articles written in English, with the purpose of future publication in international, peer-reviewed journals. In order to do so it respects some criteria related to this objective.